2020
DOI: 10.1038/s41598-020-68374-8
|View full text |Cite
|
Sign up to set email alerts
|

Sera of elderly obstructive sleep apnea patients alter blood–brain barrier integrity in vitro: a pilot study

Abstract: Obstructive sleep apnea syndrome (OSAS) is characterized by repeated episodes of hypoxia during the night. The severity of the disorder can be evaluated using an apnea–hypopnea index (AHI). The physiological consequences are mainly cardiovascular and neuronal dysfunctions. One hypothesis to explain such associated neurological disorders is disruption of the blood–brain barrier (BBB), which protects the brain from endovascular cytotoxic compounds. We selected two subgroups of volunteers from the PROOF cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…A recent review and other studies have shown that the blood–brain barrier (BBB) could be altered by several mechanisms that are present during OSA [ 78 , 79 , 80 ]. The BBB secludes the brain from the undesired transfer of substances that may be in the bloodstream while allowing the passage of nutrients that are essential for brain function.…”
Section: Impact Of Osa On Bbbmentioning
confidence: 99%
“…A recent review and other studies have shown that the blood–brain barrier (BBB) could be altered by several mechanisms that are present during OSA [ 78 , 79 , 80 ]. The BBB secludes the brain from the undesired transfer of substances that may be in the bloodstream while allowing the passage of nutrients that are essential for brain function.…”
Section: Impact Of Osa On Bbbmentioning
confidence: 99%
“…However, there is emerging evidence that the major complication of sleep loss is neuroinflammation, which induces BBB disruption (Table 1). Indeed, sleep loss per se, including sleep deprivation, sleep restriction, sleep fragmentation, or sleep apnea in human and rodents induces a systemic low-grade inflammation characterized by the release of several molecules, such as cytokines, chemokines, and acute-phase proteins; all of them can promote changes in cellular components of the BBB, particularly on brain endothelial cells [35][36][37][38][39][40][41][42][43][44][45][46]. In this session, we discuss the role of inflammatory mediators that increase during sleep loss and how these changes may alter the BBB permeability as well as we analyze hypothetical mechanisms by which sleep deprivation may induce the BBB disruption, emphasizing the regulatory effect of inflammatory molecules on tight junction proteins.…”
Section: Sleep Loss-associated Neuroinflammation and The Blood-brain Barrier Disruptionmentioning
confidence: 99%
“…Recently, it has been discovered that sleep deprivation increases the BBB permeability to inflammatory mediators, immune cells, and exogenous tracers in humans and rodents [35,36,38,39,[41][42][43]45,50,[54][55][56]. Chronic sleep restriction diminished endothelial and inducible nitric oxide synthase, endothelin1, and glucose transporter expression in cerebral microvessels of BBB and decreased 2-deoxy-glucose uptake by the brain.…”
Section: Sleep Loss-associated Neuroinflammation and The Blood-brain Barrier Disruptionmentioning
confidence: 99%
See 2 more Smart Citations